2003
DOI: 10.1097/00008480-200308000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Helping adolescents cope with stress during stressful times

Abstract: Increasing levels of stress in the daily lives of adolescents is an important health concern. Adolescents experience a variety of stressful situations and use a wide range of coping strategies to help effectively manage stress. Recent research on adolescent coping with stressful situations is reviewed. Findings support an association between coping and adolescent health problems, chronic physical illness, and mental health. More research is needed to investigate the long-term benefits of coping with stress on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Future studies should endeavor to examine how psychosocial stressors influence substance use and evaluate the long-term impact of these co-morbidities on the health outcomes of trans*female youth. In the interim, interventions that provide and support alternative coping skills may have some success in reducing substance use as a method of dealing with stressors related to gender-based discrimination (Bonica and Daniel, 2003; Goyal et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Future studies should endeavor to examine how psychosocial stressors influence substance use and evaluate the long-term impact of these co-morbidities on the health outcomes of trans*female youth. In the interim, interventions that provide and support alternative coping skills may have some success in reducing substance use as a method of dealing with stressors related to gender-based discrimination (Bonica and Daniel, 2003; Goyal et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Adolescents who learn and implement positive coping strategies are more resilient and manifest fewer mental and physical health problems. 32 School practitioners have an opportunity to engage other school staff, students, and parents in order to prevent and/or intervene in anxietyrelated symptoms (such as worries and stressors), as well as clinical anxiety disorders, thereby enabling more positive social and academic experiences for students as well as improving the overall school climate. 33 For example, 1 study found that students who participated in an 8-week program, in which school psychologists and classroom teachers taught and modeled optimistic thinking skills as part of the regular curriculum, used fewer nonproductive coping strategies, such as worrying.…”
Section: Discussionmentioning
confidence: 99%
“…Statistics are hampered by small sample sizes and lack of control groups. More comprehensive data concerning psychological, sexual, and physical well-being in adolescents with DSD are necessary to understand and respond to adolescents' needs [8,32,33].…”
mentioning
confidence: 99%